Genomic evaluation of commercial herds with different pedigree structures using the single-step genomic BLUP in Nelore cattle - Londoño-Gil, Marisol [UNESP]; Cardona-Cifuentes, Daniel [UNESP]; Espigolan, Rafael; Peripolli, Elisa [UNESP]; Lôbo, Raysildo B.; Pereira, Angélica S. C.; Aguilar, Ignacio; Baldi, Fernando (Springer Nature, 2023)
The aim of this work was to evaluate the impact of applying genomic information in pedigree uncertainty situations on genetic evaluations for growth- and cow productivity–related traits in Nelore commercial herds. Records for accumulated cow productivity (ACP) and adjusted weight at 450 days of age (W450) were used, as well as genotypes of registered and commercial herd animals, genotyped with the Clarifide Nelore 3.1 panel (~29,000 SNPs). The genetic values for commercial and registered populations were estimated using different approaches that included (ssGBLUP) or did not include genomic information (BLUP), with different pedigree structures. Different scenarios were tested, varying the proportion of young animals with unknown sires (0, 25, 50, 75, and 100%), and unknown maternal grandsires (0, 25, 50, 75, and 100%). The prediction accuracies and abilities were calculated. The estimated breeding value accuracies decreased as the proportion of unknown sires and maternal grandsires increased. The genomic estimated breeding value accuracy using the ssGBLUP was higher in scenarios with a lower proportion of known pedigree when compared to the BLUP methodology. The results obtained with the ssGBLUP showed that it is possible to obtain reliable direct and indirect predictions for young animals from commercial herds without pedigree structure.
Keywords: Beef cattle; Genomic prediction; Genomic selection; Pedigree uncertainty